Development of Student Worksheets with Learning Cycle 5E Models on Solubility Product Constant Materials and Their Influence on Student Chemistry Literacy - Maulida Ridani; Retno Arianingrum (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop a student worksheet (LKPD) based on the learning cycle 5E models. The research utilizes the 4D development model by Thiagarajan, which consists of four stages: Define, Design, Develop, and Dissemination. The sample in this study was chemistry teachers and students of SMA Negeri 1 Ngawi. The results of the validation by media and material experts indicate that the LKPD learning cycle 5E is suitable for use in learning. Readability tests conducted by students and teachers show that the LKPD learning cycle 5E falls into the "very good" category. The results of the effectiveness test, using a Mann-Whitney U test, indicate that the LKPD learning cycle 5E has a very small effect on student chemistry literacy in solubility product constant materials.